Seismic Fragility Analysis of Monopile Offshore Wind Turbines under Different Operational Conditions - Mo, Renjie; Kang, Haigui; Li, Miao; Zhao, Xuanlie (Energies (Basel), 2017)
Offshore wind turbines in seismic active areas suffer from earthquake impacts. In this study, seismic fragility analysis of a monopile offshore wind turbine considering different operational conditions was performed. A finite element model for a 5 MW monopile offshore wind turbine was developed using the OpenSees platform. The interaction between the monopile and the seabed soil was modeled as a beam-on-nonlinear-winkler-foundation (BNWF). A nonlinear time history truncated incremental dynamic analysis (TIDA) was conducted to obtain seismic responses and engineering demand parameters. Potential damage states (DSs) were defined as excessive displacement at the nacelle, rotation at the tower top, and the allowable and yield stresses at the transition piece. Fragility curves were plotted to assess the probability of exceeding different damage states. It was found that seismic responses of the wind turbine are considerably influenced by environmental wind and wave loads. Subject to earthquake motions, wind turbines in normal operation at the rated wind speed experience higher levels of probability of exceeding damage states than those in other operational conditions, i.e., in idling or operating at higher or lower wind speed conditions.